Looking for Employees Efficiency? Change the System through Value Stream Mapping (International Journal of Scientific Research and Management (IJSRM), 2019)
Inefficiency’ is considered as a buzz word with regard to the administration system of government organisations (ASGO) in Sri Lanka. Within a context of increasing annual budgetary allocation in each year, the universities are equipped with modern facilities such as information technology and continuously doing researches in different levels, conduct workshops to train employees and continuously recruit educated people. As like as the other government sectors, government universities experience inefficiency in different levels and different volumes. The inefficiency of ASGO in Sri Lanka would negatively impact on the brand identity of each organization and this study aimed to develop an efficient leave management process (LMP) for the government-university system in Sri Lanka. The key objective of the study was to propose a process map with lesser lead time instead of existing LMP of the university. The specific objectives were to recognize the existing LMP, to measure the lead time of the existing LMP, to understand the existing rules and procedures belong to leave management process and to measure the lead time of the proposed leave management process. Sample data were collected from the existing leave management process of the university in the last three years and simple statistical tools such as mean values and percentage values were associated in the analyzing process of the study. The results showed that there was a waste due to unnecessary processes and practices in the existing process and therefore it leads to inefficiency. The proposed Value Stream Map (VSM) shows lesser lead time to improve the efficiency of the LMP and then the efficiency in ASGO.